Determinants Associated with the First Dose of HPV Vaccination among Elementary School Children - Eva Dorista; Fahmi Ichwansyah; Hermansyah Hermansyah; Aripin Ahmad; Asnawi Abdullah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cervical cancer is the second leading cause of death among women in Indonesia. This health issue is actually preventable through HPV vaccination, which can be administered to 5th-grade elementary school children. Several factors influence parents' decisions not to allow their children to receive the first dose of the HPV vaccine. The aim of this study was to analyze the determinants associated with the first dose of HPV vaccination among elementary school children. This study employed a quantitative research design with a cross-sectional approach. The sample consisted of 281 mothers of 5th-grade elementary school children. Data were collected at elementary schools in Sigli City by distributing questionnaires from December 20–28, 2023. Quantitative data were analyzed using multiple logistic regression at a significance level of α=0.05 and a 95% confidence interval. The results showed that 258 children (91.81%) did not receive the HPV vaccine. Factors associated with the first dose of HPV vaccination among elementary school children were knowledge (OR=6.46; 95% CI=1.87–22.2), attitude (OR=2.74; 95% CI=1.04–7.18), concern (OR=3.31; 95% CI=1.09–10.00), and lack of utilization of information sources (OR=3.30; 95% CI=1.00–10.83). Factors not associated with the first dose of HPV vaccination included perception (OR=1.20; 95% CI=0.50–2.84), school support (OR=1.44; 95% CI=0.54–3.78), cultural beliefs (OR=1.12; 95% CI=0.47–2.63), and non-electronic media sources (OR=1.46; 95% CI=0.46–4.65). The most dominant factor associated with the first dose of HPV vaccination was poor knowledge (AOR=11.95; 95% CI=1.90–72.47).